A novel cuproptosis-related prognostic lncRNA signature for predicting immune and drug therapy response in hepatocellular carcinoma - Chen, Shujia; Liu, Peiyan; Zhao, Lili; Han, Ping; Liu, Jie; Yang, Hang; Li, Jia (Frontiers in Immunology, 2022)
Intratumoral copper levels are closely associated with immune escape from diverse cancers. Cuproptosis-related lncRNAs (CRLs), however, have an unclear relationship with hepatocellular carcinoma (HCC). Gene expression data from 51 normal tissues and 373 liver cancer tissues from the Cancer Genome Atlas database (TCGA) were collected and analyzed. To identify CRLs, we employed differentially expressed protein-coding genes (DE-PCGs) / lncRNAs (DE-lncRNAs) analysis, Kaplan Meier (K-M), and univariate regression. By univariate and lasso Cox regression analysis, we screened 10 prognosis-related lncRNAs. Subsequently, 5 CRLs were identified by multivariable Cox regression analysis to construct the prognosis model. This feature is an independent prognostic indicator to forecast overall survival (OS). According to Gene Set Enrichment Analysis (GSVA) and Gene Ontology (GO), both immune-related biological processes (BPS) and pathways have CRLs participation. In addition, we found that the characteristics of CRLs were associated with the expression of the tumor microenvironment (TME) and crucial immune checkpoints. CRLs could predict the clinical response to immunotherapy based on studies of tumor immune dysfunction and rejection (TIDE) analysis. Additionally, it was verified that tumor mutational burden (TMB) survival and prognosis were greatly different between high-risk and low-risk groups. Finally, we screened potential sensitive drugs for HCC. In conclusion, this study provides insight into TME status in patients with HCC and lays a basis for immunotherapy and the selection of sensitive drugs.